Advanced Simulation and Analysis of MIMO Dead Time Compensator and Predictive Controller for Ethanol Distillation Process. Issue 1 (2019) - Pataro, Igor M.L.; da Costa, Marcus V. Americano; Joseph, Babu
Abstract: This paper analyses advanced control strategies in an ethanol production facility. A Matlab computing platform integrated with Aspen Hysys was developed to simulate industry practice. Two types of advanced control system were used in this study: a Model Predictive Control and a Dead Time Compensator. In particular, an Infinite Horizon Predictive Controller (IHMPC) and Filtered Smith Predictor (FSP) controller were designed to ensure ethanol production into a desired quality range under feed variations as disturbances. Performance indexes and computational processing time were used to evaluate the control systems. This work offers different and satisfactory solutions for several application scenarios, taking in account the main characteristics of each controller.